Biphasic Malignant Pleural Mesothelioma Masquerading as a Primary Skeletal Tumor - James Benjamin Gleason; Basheer Tashtoush; Maria Julia Diacovo (Case Reports in Pulmonology)
Biphasic malignant pleural mesothelioma is a rare malignant tumor, usually presenting as a pleural-based mass in a patient with history of chronic asbestos exposure. We herein report a case of a 41-year-old man who presented with chest pain and had a chest computed tomography (CT) scan suggestive of a primary skeletal tumor originating from the ribs (chondrosarcoma or osteosarcoma), with no history of asbestos exposure. CT-guided core needle biopsies were diagnosed as malignant sarcomatoid mesothelioma. Surgical resection and chest wall reconstruction were performed, confirming the diagnosis and revealing a secondary histologic component (epithelioid), supporting the diagnosis of biphasic malignant mesothelioma.